Просторова будова та електронні спектри поглинання наночастинок неорганічного пігменту ортованадату бісмуту - Гребенюк, А. Г. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2025)
In recent years, researchers have focused their attention on the creation and study of the properties of relatively low-toxic pigments based on mixed oxides, in particular, yellow bismuth orthovanadate BiVO4, using experimental and theoretical methods. The work performes a systematic quantum chemical analysis of the spatial structure and energy characteristics, as well as electronic absorption spectra of molecular models for this substance with the zircon ZrSiO4 structure ZrSiO4, which consist of 1–14 formula units. The structure and properties of the considered molecular models were studied by the method of electron density functional theory within both stationary (DFT) and non-stationary (TDDFT) versions with the SBKJC basis set using the PC GAMESS software package. Equilibrium molecular models contain tricoordinate oxygen atoms adjacent to tetracoordinate vanadium atoms and octacoordinate bismuth atoms (some of the bismuth atoms on the cluster surface may have lower coordination numbers). Simple chains of bismuth orthovanadate, which include 1, 2, and 3 formula units of the substance, are too small to reflect the properties of polymorphic modifications of the substance. In model structures formed by closely spaced simple chains, the coordination number of vanadium atoms remains 4, and their length is 1.692–1.723 Å, while bismuth atoms increase the coordination number up to 8 (with the length of the 6 Bi-O bonds increasing to 2.300–2.460 Å and a pair of short contacts of 2.900 Å being added). The energy gap width of these particles decreases, which corresponds to a bathochromic shift of the maxima in the electronic absorption spectra of the models, and maxima appear in the visible range, which correspond to a yellow color, consistent with the experiment. The impurity phase of bismuth orthovanadate in the isostructural environment of colorless zircon was mimicked by a structure containing 14 formula units. The results of the calculations show that the models with highly coordinated bismuth atoms in the center of the cluster have almost the same energy gap values, and narrow bands are present in the corresponding electronic absorption spectra, corresponding to the yellow-orange color, and the dilution of bismuth orthovanadate in the isostructural zircon matrix increases the intensity of the pigment color.